Solvent-less solid state synthesis of dispersible metal and semiconducting metal sulfide nanocrystals - Bera, Abhijit; Busupalli, B.; Bhagavatula L. V. Prasad (ACS sustainable chem. eng, 2018)
Monolayer protected metal and metal sulfide nanocrystals (NCs) have mainly two constituents; the inorganic metal or metal chalcogenide complex as core and organic molecule as shell. Noticing that metal thiolates have these ingredients inbuilt in their structure, we investigated them as possible precursors for the preparation of monolayer protected metal and metal sulfide NCs via solid state grinding method. Accordingly silver and gold NCs have been prepared using a solvent less green approach, by the simple and convenient solid state grinding of the corresponding metal thiolate with sodium borohydride. Similarly, a large variety of uniform-sized semiconducting NCs of metal sulfides including PbS, CdS, ZnS, MnS, Ag2S, and CuS could also be synthesized by the same solid state route by grinding the metal thiolates with octyl dithiocarbamic acid (C8DTCA) and in some cases C8DTCA plus small amount of oleylamine as sulfur source. Interestingly, this simple technique could be used to prepare sub-3 nm NCs like Ag2S, PbS, and CuS which are otherwise difficult to prepare by the conventional high temperature solution routes also. Most gratifyingly, all these NCs, though were prepared by a solvent less grinding method, could be easily dispersed in nonpolar solvents as the preparation method ensued the formation of organic molecule capped NCs.